Bruxism: etiopathogenesis, diagnosis and its repercussions in adults. Review of the literature - Cifuentes-Harris, Carla Beatriz (2022)
Bruxism is defined as a repetitive muscular activity of the jaw, characterized by clenching, or grinding of the teeth due to dragging or thrusting of the jaw. It can manifest itself during sleep or wakefulness. The aim of this review is to establish the most important aspects of bruxism in adults, focusing on its etiology, diagnosis, and its repercussions in adults. The prevalence of sleep bruxism among adults ranges from 22% to 30% and between 1% to 15% for bruxism during wakefulness. Its etiology is associated with two groups of factors: central (psychological and pathophysiological) and peripheral (morphological). In diagnostic methods, it is found as possible (non-instrumental approach or self-report), probable (self-report and clinical examination) or definitive (self-report, clinical examination and polysomnography). The gold standard for the diagnosis of sleep bruxism is polysomnography. In terms of its repercussions, we can find different types of dental hard tissue lesions, mainly abfractions, attrition and mixed lesions. At the musculoskeletal level, the evidence is contradictory as it has been associated with muscle fatigue, sensitivity, and tension, but there is no linear cause-effect relationship. A direct and statistically significant relationship exists between sleep bruxism and morning headaches.